2016
DOI: 10.1093/gbe/evw163
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling in the Hibernating Primate,Cheirogaleus Medius

Abstract: Hibernation is a complex physiological response that some mammalian species employ to evade energetic demands. Previous work in mammalian hibernators suggests that hibernation is activated not by a set of genes unique to hibernators, but by differential expression of genes that are present in all mammals. This question of universal genetic mechanisms requires further investigation and can only be tested through additional investigations of phylogenetically dispersed species. To explore this question, we use RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 82 publications
1
30
1
Order By: Relevance
“…This enzyme inhibits carbohydrate catabolism by preventing the conversion of pyruvate to acetyl‐CoA (Buck et al., ). Shallow torpor under laboratory conditions also induces PDK4 , in agreement with a previous study conducted at the Duke Lemur Center (Durham, NC, USA) with dwarf lemurs of the species Cheirogaleus medius (fat‐tailed dwarf lemurs; Faherty, Villanueva‐Cañas, et al., ). The present study provided a unique opportunity to investigate whether similar changes occurred in dwarf lemurs undergoing torpor in the wild.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…This enzyme inhibits carbohydrate catabolism by preventing the conversion of pyruvate to acetyl‐CoA (Buck et al., ). Shallow torpor under laboratory conditions also induces PDK4 , in agreement with a previous study conducted at the Duke Lemur Center (Durham, NC, USA) with dwarf lemurs of the species Cheirogaleus medius (fat‐tailed dwarf lemurs; Faherty, Villanueva‐Cañas, et al., ). The present study provided a unique opportunity to investigate whether similar changes occurred in dwarf lemurs undergoing torpor in the wild.…”
Section: Resultssupporting
confidence: 90%
“…This study demonstrates why some studies, such as those on hibernation physiology, are best conducted in the field under entirely natural conditions, at least in critically endangered lemur species. Although acknowledging the difficulty of tracking animals, variables that cannot be controlled as well as under laboratory settings, and overall challenging working conditions, our field study uncovered more genes that were found to be differentially expressed when comparing our former captive study with dwarf lemurs at the Duke Lemur Center (Faherty, Villanueva‐Cañas, et al., ). In both studies, differential expression was investigated using four individuals.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…), [108][109][110][111][112] American black bears (Ursus americanus), 113,114 little brown bats (Myotis lucifugus) 115 and recently in two different species of dwarf lemurs (Cheirogaleus medius and Cheirogaleus crossleyi). 21,116 These studies reveal specific genes that might play a key role in the hibernation phenotype and similar pathways are upregulated in predictable ways in all hibernating species studied to date. Of import are genes involved in lipid and carbohydrate metabolism, blood coagulation, and circadian rhythms.…”
Section: Box 3 Genetic Basis Of Hibernationmentioning
confidence: 95%